2019
DOI: 10.1101/737312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single unit activity in marmoset posterior parietal cortex in a gap saccade task

Abstract: Abnormal saccadic eye movements can serve as biomarkers for patients with several neuropsychiatric disorders. To investigate cortical control mechanisms of saccadic responses, the common marmoset (Callithrix jacchus) is a promising non-human primate model. Their lissencephalic brain allows for accurate targeting of homologues of sulcal areas in the macaque brain. Here we recorded single unit activity in the posterior parietal cortex of two marmosets using chronic microelectrode arrays, while the monkeys perfor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…On the other hand, the area surrounding the marmoset IPS have also been linked to the attention-like frontoparietal network by several RS-fMRI studies (Ghahremani et al, 2016; Hori et al, 2020b). It is also known that electrical microstimulation in the areas surrounding the IPS evoke saccadic eye movements (Ghahremani et al, 2019) and that single neurons in the region show neural correlates for the gap effect in saccadic eye movement tasks (Ma et al, 2020). As such, it seems that parietal areas surrounding the IPS in the marmoset are involved in both default mode and attention networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the area surrounding the marmoset IPS have also been linked to the attention-like frontoparietal network by several RS-fMRI studies (Ghahremani et al, 2016; Hori et al, 2020b). It is also known that electrical microstimulation in the areas surrounding the IPS evoke saccadic eye movements (Ghahremani et al, 2019) and that single neurons in the region show neural correlates for the gap effect in saccadic eye movement tasks (Ma et al, 2020). As such, it seems that parietal areas surrounding the IPS in the marmoset are involved in both default mode and attention networks.…”
Section: Discussionmentioning
confidence: 99%
“…The common marmoset has become an important nonhuman primate model for bridging the translational gap between rodents and humans. Marmosets have a lissencephalic cortex, like rodents, but as primates they possess the structural and functional brain architecture that supports elaborated behaviors such as pro-social interaction (Ferrari and Digby, 1996; Huang et al, 2020; Miller et al, 2016; Saito, 2015; Yokoyama and Onoe, 2015), complex vocal communication (Choi et al, 2015; Miller et al, 2015; Sadagopan et al, 2015; Takahashi et al, 2016), and saccadic eye movements (Chen et al, 2020; Ma et al, 2020; Mitchell et al, 2014; Selvanayagam et al, 2019). This, paired with a high reproductive power, small size, and fast maturation rate, make this non-human primate (NHP) species particularly interesting for neuroscience.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological recordings in macaque area LIP have also revealed that most neurons discharge in the 'planning stage', just prior to the execution of saccades towards visible and remembered visual targets (Gnadt and Andersen 1988;Barash et al 1991;Colby et al 1996;Meister et al 2013) within their response fields. For example, during saccade tasks where the end target onset is delayed after the fixation target disappears, a "gap effect" of shorter saccade reaction times coupled with an increase in neural activity during the gap period has been recorded in macaques (Chen et al 2013(Chen et al , 2016 as well as marmosets (Ma et al 2020). Generally, area LIP neurons respond to a combination of visual stimuli, eye position and the direction and amplitude of planned eye movements, to encode the location of salient visual stimuli in eye-centered or headcentred coordinates (Andersen et al 1985(Andersen et al , 1990b.…”
Section: Key Areas In the Frontal-parietal Network Are Conserved In Marmosets And Macaquesmentioning
confidence: 99%
“…Express saccades, or saccades with very low latencies, can be elicited using a 'gap' saccade task, in which the central fixation point disappears prior to the saccade target onset. Humans, macaques, and marmosets all exhibit low-latency express saccades in a gap-saccade task (Ma et al 2020;Chen et al 2021). Marmosets can also perform smooth pursuit eye movements, in which the eye voluntarily tracks a moving target, with similar velocity and acceleration profiles to macaques and humans .…”
Section: Marmosets Are Capable Of a Wide Range Of Visual Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation